2014
DOI: 10.1007/s10342-014-0853-z
|View full text |Cite
|
Sign up to set email alerts
|

Post-dispersal predation of Pinus pinaster Aiton seeds: key factors and effects on belowground seed bank

Abstract: Seed bank dynamics constitute a pool of natural regeneration, a complex and key process for stand persistence. The present work analyses post-dispersal predation on a density. These results demonstrate how seed rain, summer drought and micro-site conditions are crucial to understanding the effects of predation on the below-ground seed bank. Though greater than null, the final seed bank might be insufficient for successful natural regeneration due to high mortality caused by difficult germination and establishm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 35 publications
0
20
0
1
Order By: Relevance
“…The lessened seedling recruitment after two fire events in our study site was not fully compensated by the manual spreading of seeds after fire, as most scattered seeds following contour lines were dragged by rainfall towards the bottom of the slopes (personal observation) (see e.g., Espelta et al, 2003). Many additional factors might have also contributed to weaken the effectiveness of direct seeding and to impede seedling establishment, such as post-dispersal seed predation (Ruano et al, 2015), the high percentage of the surface covered by stones and the low coverage of fine woody debris [i.e., downed branches and pieces of dead wood <2 cm diameter, and remaining unburned foliage; 7.95 ± 10.14 and 0.49 ± 0.45 at stands subjected to one and two fires, respectively; unpublished data] (Madrigal et al, 2005;Rodríguez et al, 2008;Rodríguez-García et al, 2010). Yet, in these stands subjected to repeated large fires, average seedling density was either similar or superior to that at the abovementioned experimental plots where burned wood was removed or fully/partly left onsite (Castro et al, 2011), and may be sufficient to ensure post-fire regeneration (Gil et al, 2009).…”
Section: Discussionmentioning
confidence: 87%
“…The lessened seedling recruitment after two fire events in our study site was not fully compensated by the manual spreading of seeds after fire, as most scattered seeds following contour lines were dragged by rainfall towards the bottom of the slopes (personal observation) (see e.g., Espelta et al, 2003). Many additional factors might have also contributed to weaken the effectiveness of direct seeding and to impede seedling establishment, such as post-dispersal seed predation (Ruano et al, 2015), the high percentage of the surface covered by stones and the low coverage of fine woody debris [i.e., downed branches and pieces of dead wood <2 cm diameter, and remaining unburned foliage; 7.95 ± 10.14 and 0.49 ± 0.45 at stands subjected to one and two fires, respectively; unpublished data] (Madrigal et al, 2005;Rodríguez et al, 2008;Rodríguez-García et al, 2010). Yet, in these stands subjected to repeated large fires, average seedling density was either similar or superior to that at the abovementioned experimental plots where burned wood was removed or fully/partly left onsite (Castro et al, 2011), and may be sufficient to ensure post-fire regeneration (Gil et al, 2009).…”
Section: Discussionmentioning
confidence: 87%
“…the percentage of serotinous cones varies among individuals of the same population and among different populations) (Tapias et al 2001(Tapias et al , 2004, which is a heritable character (Hernández-Serrano et al 2014) closely related to the type of fire regime affecting each population (Hernández-Serrano et al 2013;Tapias et al 2004). Serotiny acts as an advantageous reproductive adaptation of P. pinaster populations in fire-prone environments, because (1) the canopy seed bank of the species is relatively small in non-serotinous populations (Tapias et al 2001), and (2) the soil seed bank is insufficient and temporary and ends up irreversibly damaged either by fire-induced temperatures or by post-dispersal predation (De las Heras et al 2012;Ruano et al 2015;Torres et al 2006). Populations with high levels of serotiny can retain closed cones up to 40 years and preserve seed viability for 30 years (Tapias et al 2004) and are, therefore, more likely to survive frequent crown fires and achieve successful post-fire recruitment (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, climate variability influences predator populations, showing larger rates in autumn-winter and almost no predation in summer. As for P. pinea, predation is favoured in the vicinity of stumps and in denser areas (potential sheltered locations), while the presence of grasses and needles on the floor hide seeds and therefore prevents predation (Ruano et al, 2014).…”
Section: Pre and Post-dispersal Seed Predationmentioning
confidence: 99%
“…Ruano et al (2014) showed that predation can reduce seed density up to values below 1 seed/m 2 , even in locations where seed rain reached values over 40-50 seeds/m 2 . Although no specific experiment for detecting potential predators' species was carried out, the authors indicate that together with A. sylvaticus, C. ciyanus and C. corax, ants should be considered a potential predator for the seed of P. pinaster.…”
Section: Pre and Post-dispersal Seed Predationmentioning
confidence: 99%